2018
DOI: 10.3390/ma11050717
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Conversion between Different Compounds of Ternary Cs-Pb-Br System

Abstract: The perovskite CsPbBr3 attracts great attention due to its potential in optoelectronics. However, stability remains a major obstacle to achieving its effecting application. In this work, we prepared CsPbBr3 solids through a simple reaction and investigated reversible conversion between CsPbBr3, Cs4PbBr6, and CsPb2Br5. We found that CsPbBr3 can be respectively converted to Cs4PbBr6 or CsPb2Br5 by reacting with CsBr or PbBr2. Thermodynamic analysis demonstrated that the chemical reactions above were exothermic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…The most common example is the 3D → 0D (CsPbBr 3 → Cs 4 PbBr 6 ) NC transformation. 307 311 This is triggered by the extraction of PbBr 2 from the 3D CsPbBr 3 perovskite NCs that are operated by the excess amines. 70 , 307 It has been reported that, by adding alkyl-thiol ligands, the size uniformity and chemical stability of the as-transformed Cs 4 PbBr 6 NCs can be greatly improved.…”
Section: Surface Shape and Phase Postmodificationsmentioning
confidence: 99%
“…The most common example is the 3D → 0D (CsPbBr 3 → Cs 4 PbBr 6 ) NC transformation. 307 311 This is triggered by the extraction of PbBr 2 from the 3D CsPbBr 3 perovskite NCs that are operated by the excess amines. 70 , 307 It has been reported that, by adding alkyl-thiol ligands, the size uniformity and chemical stability of the as-transformed Cs 4 PbBr 6 NCs can be greatly improved.…”
Section: Surface Shape and Phase Postmodificationsmentioning
confidence: 99%
“…High incident angle (2°) XRD analyses confirmed the phase purity in the bulk of the CSS‐deposited CsPbBr 3 films (Figure S1, Supporting Information) with the orthorhombic perovskite structure. [ 8,9,12,23 ] No diffraction peaks for polymorphs Cs 4 PbBr 6 and CsPb 2 Br 5 [ 24 ] (Figure S2, Supporting Information) were observed, further demonstrating the phase purity of the deposited CsPbBr 3 films. The crystallite size of the as‐deposited CsPbBr 3 was in the range of ≈245 nm with lattice constants a = 8.205, b = 11.694, and c = 8.268 Å, consistent with the orthorhombic CsPbBr 3 phase.…”
Section: Cspbbr3 Film Deposition Using Close Space Sublimationmentioning
confidence: 99%
“…By changing the amount of bromine, we acquired different products. In the case of Cs:Pb:Br=1:6:6, the absorption peak is at 340 nm and there is no PL‐emission peak, which is could be due to formation of the nonluminescent CsPb 2 Br 5 phase of the perovskite NCs [37] . On increasing the Br concentration, CsPbBr 3 NCs are formed, which emit green light under UV irradiation.…”
Section: Resultsmentioning
confidence: 99%